ARTICLE APPLICATION PAPER 2 - Alexander, Susan (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
The second sets of readings centers around the question, "Why do consumers go along with the corporate ideology?" All the theorists in this section believe people go along with corporate ideology because the producers have embedded social meaning into a product. Thus, people are "consuming" a meaning rather than a product. Specifically, Baudrillard argues that producers construct a product as fulfilling a "need," and it is important for individual to learn to deconstruct this social process. Goldman and Papson analyze the process of creating a "commodity sign" which is comprised of the brand name commodity plus the meaning of the images attached to the object. Finally, Bordo examines how the social meanings attached to products are gendered and thus target a particular consumer through her discussion of female hunger and weight in advertising.Select one of the options below for your paper topic: